Putting the New Keynesian DSGE model to the real-time forecasting test - Marcin Kolasa; Michał Rubaszek; Paweł Skrzypczyński (European Central Bank (ECB), 2009)
Dynamic stochastic general equilibrium models have recently become standard tools for policy-oriented analyses. Nevertheless, their forecasting properties are still barely explored. We fill this gap by comparing the quality of real-time forecasts from a richly-specified DSGE model to those from the Survey of Professional Forecasters, Bayesian VARs and VARs using priors from a DSGE model. We show that the analyzed DSGE model is relatively successful in forecasting the US economy in the period of 1994-2008. Except for short-term forecasts of inflation and interest rates, it is as good as or clearly outperforms BVARs and DSGE-VARs. Compared to the SPF, the DSGE model generates better output forecasts at longer horizons, but less accurate short-term forecasts for interest rates. Conditional on experts' now casts, however, the forecasting power of the DSGE turns out to be similar or better than that of the SPF for all the variables and horizons.
Keywords: C11; C32; C53; D58; E17; 330; Bayesian VAR; DSGE; forecasting; real-time data; SPF; Neoklassische Synthese; Frühindikator; Dynamisches Gleichgewicht; Prognoseverfahren; Bayes-Statistik; VAR-Modell; USA